∫ 1 1 6 tan − 1 x − 1 d x
Given that the integral above is equal to a π − 2 b , where a and b are rational numbers, find the value of a × b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can also substitute x = sec 4 t
Sir,It may be done by partial integration after taking x = ( t + 1 ) 2 ? (as you have mentioned)
∫ 1 1 6 arctan x − 1 d x
Put x = sec 4 θ ⇒ d x = 4 sec 4 θ tan θ d θ
∫ 0 3 π 4 θ sec 4 θ tan θ d θ
Using product rule,
4 θ ∫ sec 2 θ tan θ sec 2 θ d θ ) − 4 ∫ 0 3 π ∫ sec 2 θ tan θ sec 2 θ d θ d θ ⇒ 4 θ ∫ ( tan 2 θ + 1 ) tan θ sec 2 θ d θ ) − 4 ∫ 0 3 π ∫ ( tan 2 θ + 1 ) tan θ sec 2 θ d θ d θ ⇒ 4 θ ( 4 tan 4 θ + 2 tan 2 θ ) − 4 ∫ 0 3 π ( 4 tan 4 θ + 2 tan 2 θ ) d θ ⇒ θ tan 4 θ + 2 θ tan 2 θ − ∫ 0 3 π ( tan 2 θ ) ( tan 2 θ + 2 ) d θ ⇒ θ tan 4 θ + 2 θ tan 2 θ − ∫ 0 3 π tan 2 θ ( sec 2 θ + 1 ) d θ ⇒ θ tan 4 θ + 2 θ tan 2 θ − ∫ 0 3 π tan 2 θ sec 2 θ d θ − ∫ 0 3 π sec 2 θ d θ + ∫ 0 3 π d θ ⇒ θ tan 4 θ + 2 θ tan 2 θ − 3 tan 3 θ − tan θ + θ
Now, inserting limits,
3 π ( 9 ) + 2 3 π ( 3 ) − 3 − 3 + 3 π − 0 = 3 1 6 π − 2 3 a = 3 1 6 , b = 3
And, you can do the math! :)
Did the same!
Let p = x − 1 . Put x = 1 6 to get p = 3 and x = 1 to get p = 0
Meanwhile, x = ( p 2 + 1 ) 2 and d x = ( 4 p 3 + 4 p ) d p .
Now, we have new integration:
I = ∫ 0 3 ( 4 p 3 + 4 p ) tan − 1 p d p
We will apply integration by parts to solve I .
Let,
u = tan − 1 p , then d u = p 2 + 1 d p
v = ∫ 4 p 3 + 4 p d p = p 4 + 2 p 2
I = ( p 4 + 2 p 2 ) tan − 1 p − ∫ ( p 2 + 1 ) − p 2 + 1 1 d p = ( p 2 + 1 ) 2 tan − 1 p − ( 3 p 3 + p )
Subtitution p = 3 and p = 0 to find out the result of I .
I = 1 6 × 3 π − 2 3 − 0 = 3 1 6 × π − 2 3
Now, we just yield the required answer, a × b = 1 6
For ∫ 1 1 6 T A N − 1 x − 1 d x
∫ 1 1 6 T A N − 1 x − 1 d x = − 3 1 ( 3 x − 1 ) − x − 1 + x T A N − 1 ( x − 1 ) + C Indefinite = 3 1 6 π − 2 3
where a = 3 1 6 and b = 3
∴ a ⋅ b = 1 6 □
ADIOSS!!!
Great, thanks!
Log in to reply
Gladly accepted Sir! I'm running out of time to full my step-by-step computation.
ADIOS!!!
What's this??
How u have tan inverse in 3 parts ??
Hint: Substitute x = ( z 2 + 1 ) 2 , then apply Integration by parts, we find a = 3 1 6 and b = 3 .
So, a b = 1 6
improve more
Problem Loading...
Note Loading...
Set Loading...
Hint: Substitute x = ( t + 1 ) 2 , then apply Integration by parts to get a = 3 1 6 , and b = 3